Evaluation of Aqueous Extract from Cosmos caudatus Leaves in Alloxan-Induced Diabetic Rats - Rosdah, Ayeshah Augusta; Natasha, Amanda; Tamzil, Nia Savitri; Subandrate, Subandrate (Borneo Journal of Pharmacy, 2025)
Kenikir (Cosmos caudatus), often consumed as a vegetable in Southeast Asia, possesses therapeutic benefits for several diseases, including diabetes mellitus. However, there has been limited investigation of the aqueous extract of C. caudatus for this disease model. This study aimed to examine the glucose-lowering effect of C. caudatus aqueous extract in an alloxan-induced diabetes model in rats. Ultrasound-assisted extraction was performed to obtain an aqueous extract of C. caudatus leaves. Qualitative phytochemical screening was carried out to identify the presence of bioactive compounds. Male Wistar rats were allocated to the following experimental groups: non-diabetic, diabetic without treatment, and diabetic treated with glibenclamide or aqueous C. caudatus extract at concentrations of 25%, 50%, or 100%. Diabetes was induced by intraperitoneal injection of 150 mg/kg alloxan. Random blood glucose and body weight were monitored before (Day 0) and after treatment (Days 3 and 7). There was a trend of weight loss in diabetic rats compared to non-diabetic rats, though the difference was not statistically significant. After 7 days of treatment, there was a comparable decrease in the blood glucose of diabetic rats treated with 50% or 100% of aqueous C. caudatus extract and those treated with glibenclamide. Qualitative phytochemical screening indicated the presence of steroid, saponin, phenol, and flavonoid compounds. The total phenolic content was 38.48 mg GAE/g and IC50 DPPH antioxidant activity was 375.64 ppm. This study demonstrated that an aqueous extract of C. caudatus exhibits a blood glucose-lowering effect in an alloxan-induced diabetic rat model.